Polesė – „pamiškė“, „palenkė“ ar „didelių pelkių kraštas“? - Laučiūtė, Jūratė Sofija (Baltistica, 2006)
POLESIE: “ALONG THE FOREST“, „ALONG THE VALLEY“ OR „LAND OF GREAT SWAMPS“? Polesie is a territory inhabited by speakers of an Eastern Slavonic dialect called „Poleshuk“, stretching across southern Belarus, northern Ukraine, several neighboring western regions of Russia and part of the western headwaters of Poland’s section of the Pripet River. The Polesie region is extremely significant for the history of old contacts between Balts and Slavs, because of its linguistic peculiarities and archaeological monuments, which offer evidence that this could have been the zone where Balts and Slavs first met, the strongest traces of which were impressed in the local place names. The abundance of Baltic traces in the Polesie region calls for greater attention to the origin of the name Polesie itself. This article presents arguments casting doubt on the Slavic origin of the name: supposedly Polesie = Slav. (R.) po- + les- (по- + лес-) „along the forest“, from R. лес „forest“, cf. по-бережье „along the shore“, etc. Even those linguists who tend toward maintaining that the etymology is based on „forest“ try to connect Polesie with Baltic hydronyms such as Pala, Pelesa and others, which etymologically have nothing in common with the meaning „forest.“ Based on appellative and onomastic constructions of the Baltic pal-/pel- root and borrowings of these in the Slavic languages, it is suggested that the proper name Polesie needs to be considered as part of the heritage of the Baltic substrate, a word whose „ancestors“ could have been either a hydronym with the affix -es- (e.g., Pelesa), or a geographic term meaning „large swamp“, cf. Lith. palà „marsh or morass, bog, swamp“, palios „large swamp in places where lakes have been overgrown, wasteland“, Latv. palas, paļas „marshy lake shore“ and others. Similar typological/semantic parallels exist in other regions, cf. Pannonia „historical Roman province in the area of the present-day lake Balaton“, whose title *Pannona is sought in the appellative meaning of „swamp, bog“ in the Illyrian language, cf. Baltic (Prussian) pannean „swamp“. A Baltic origin for Polesie is also strengthened by the fact that a large portion of the borrowings from the Baltic substrate in the various Eastern Slavonic languages are comprised of words for wet, low and swampy places, e.g.: alos, алес „swamp, marsh, quagmire“ (Polish, Belarusian, Russian, Ukrainian); kudra, кудра „forest in a swamp, small lake“ (Polish, Belarusian, Rus., Ukr.); pelka, пелька „swamp, depression“ (cf. Lith. pelkė „swamp“) (Polish, Belarusian, Rus., Ukr.); rojst(o), ройст(а) „swampy place, bog, fen“ (Polish, Belarusian, Rus.); твань/тваль „swampy place, quagmire“; R. пурвиж „peatbog“, банда „an overgrown lake filled with crucian carp)“, лом(a)/(o) ламы́ „swamp, bog, fen, marshy meadow“, дребь/дреб „fen, swampy place overgrown with forest“ and so on. In light of the semantic/typological, etymological and areal features of the toponym Polesie there is strong basis to the claim that it is of Baltic origin and possibly meant „land of great swamps“, while the semantic connections with „forest“ arose later, following inhabitation of the land by the Eastern Slavic tribes and their adoption of the local Baltic toponyms.